2018 IEEE International Symposium on Circuits and Systems (ISCAS) 2018
DOI: 10.1109/iscas.2018.8351546
|View full text |Cite
|
Sign up to set email alerts
|

An 826 MOPS, 210uW/MHz Unum ALU in 65 nm

Abstract: To overcome the limitations of conventional floatingpoint number formats, an interval arithmetic and variablewidth storage format called universal number (unum) has been recently introduced [1]. This paper presents the first (to the best of our knowledge) silicon implementation measurements of an application-specific integrated circuit (ASIC) for unum floating-point arithmetic. The designed chip includes a 128-bit wide unum arithmetic unit to execute additions and subtractions, while also supporting lossless (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…This architecture only instantiates one coprocessor 4 ○. The coprocessor scratchpad hosts gbounds, and the main memory 5 ○ hosts UNUMs/ubounds. The conversion between those two formats is handled, during load and store operations, by a dedicated Load and Store Unit (LSU, 3 ○).…”
Section: Smurf Micro-architecture Hardware Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…This architecture only instantiates one coprocessor 4 ○. The coprocessor scratchpad hosts gbounds, and the main memory 5 ○ hosts UNUMs/ubounds. The conversion between those two formats is handled, during load and store operations, by a dedicated Load and Store Unit (LSU, 3 ○).…”
Section: Smurf Micro-architecture Hardware Implementationmentioning
confidence: 99%
“…The coprocessor is interfaced, through the RoCC interface 4 ○, with the main core (instructions and data ports) and with the memory (cache L1). In 1 ○, the control unit 5 ○ decodes the input instruction and generates the control words for the decode and execute stages. 1 ○ hosts the gbound Register File 6 ○ (gRF, Section 3).…”
Section: Smurf Micro-architecture Hardware Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…In that work, the authors showed a save of 80% of storage space with respect the use of Floats, without loosing in accuracy. • Hardware implementations: Type-I Unums have been recently implemented in hardware, on FPGA [16,22]. The authors conclude that implementing in hardware Type-I Unums requires a bigger area than that of an FPU.…”
Section: A Type-i Unumsmentioning
confidence: 99%
“…We use a Julia-based emulator on a conventional CPU, as posit hardware is not yet available. Posit research currently focuses on hardware implementations [6,7,12,32].…”
mentioning
confidence: 99%